Atmospheric Iron and Aluminium Deposition and Sea-Surface Dissolved Iron and Aluminium Concentrations in the South China Sea off Malaysia Borneo (Sarawak Waters) - Farah Akmal, Idrus; Khairul Nizam, Mohamed; Nur Syazwani, Abdul Rahim; Melissa, Dennis Chong (UNIMAS Publisher, 2021)
South China Sea (SCS) is an oligotrophic sea which usually receives low nutrients supply. However, massive atmospheric dust input was occurred during the haze event in Southeast Asia for almost every year. The input of dissolved iron (DFe) and dissolved aluminium (DAl) from dust and nearby land into SCS off Sarawak Borneo region during the worst haze event in 2015 of the Southeast Asia were investigated. The estimation dust deposition during this study was 0.162 mg/m2/yr. The atmospheric fluxes of total Fe and total Al at the offshore Sarawak waters were 0.611 µmol/m2/yr and 2.03 µmol/m2/yr, respectively, where the readily available dissolved Fe and Al from the dust were 0.11 µmol/m2/yr (DFe) and 0.31 µmol/m2/yr (DAl). Fe has higher solubility (17.78%) than Al (15.21%). The lateral fluxes (e.g. from the nearby land) were 37.08 nmol/m2/yr (DFe) and 125 nmol/m2/yr (DAl), with strong Fe organic ligand class L1 (log K:22.43 – 24.33). High concentrations of DFe and DAl at the surface water of the offshore region, coincided with high concentration of macronutrients due to the prevailing south-westerly winds originated from the west Kalimantan. Low residence times, ~0.92 (DFe) and ~1.31 (DAl) years, corresponded well with DAlexcess in surface seawater due to biological utilization of DFe. Future works emphasize on natural organic Fe(III) ligands and phytoplankton study are needed for better understanding on biogeochemistry of Fe and Al at SCS off Malaysia Borneo.